Enzymes Encapsulated within Alginate Hydrogels: Bioelectrocatalysis and Electrochemiluminescence Applications - Simona Ferraraccio (Analytical Chemistry, 2022)
A simple procedure to incorporate enzymes (horseradish peroxidase, HRP, and lactate oxidase, LOx) within alginate hydrogels is reported with electrochemiluminescence (ECL) used to detect the enzymatic reactions with the corresponding substrates. First, HRP and LOx were successfully immobilized into CaCO3 microspheres, followed by the electrostatic layer-by-layer deposition of a nanoshell onto the microspheres, and finally by their dispersion into alginate solution. The as-prepared dispersion was drop cast onto the glassy carbon electrodes and cross-linked by the external and internal gelation methods using Ca2+ cations. The enzymes encapsulated within the alginate hydrogels were characterized using cyclic voltammetry and kinetic studies performed using ECL. The results showed that the enzymatic activity was significantly maintained as a result of the immobilization, with values of the apparent Michaelis–Menten constants estimated as 7.71 ± 0.62 and 8.41 ± 0.43 μM, for HRP and LOx, respectively. The proposed biosensors showed good stability and repeatability with an estimated limit of detection of 5.38 ± 0.05 and 0.50 ± 0.03 μM for hydrogen peroxide and lactic acid, respectively. The as-prepared enzymes encapsulated within the alginate hydrogels showed good stability up to 28 days from their preparation. The sensitivity and selectivity of the enzymes encapsulated within the alginate hydrogels were tested in real matrices (HRP, hydrogen peroxide, in contact lens solution; LOx, lactic acid in artificial sweat) showing the sensitivity of the ECL detection methods for the detection of hydrogen peroxide and lactic acid in real samples.